Why do worms go against the flow? C. elegans behaviors explained by simple physics - Bau, Haim H (Worm, 2015)
Nearly half a century of neurobiological research using the nematode Caenorahbitis elegans has produced a remarkably detailed understanding of how genotype controls behavioral phenotype. However, the role of simple physical forces in regulating behavior has been understudied. Here, we review our recent observations of 3 behaviors of C. elegans suspended in solution that can be fully explained by the laws of mechanics. These behaviors are bordertaxis, the attraction toward solid surfaces; positive rheotaxis, the propensity to swim against the flow; and synchrophilia, the tendency of animals when close to each other to synchronize their gaits. Although these 3 behaviors are not directly regulated by the animal's nervous system, bordertaxis and rheotaxis require the animal to have an undulating gait. We conjecture that these behaviors are advantageous to the animals, and thus evolution may have favored microorganism that swim with an undulating gait.